Does servant leadership style induce positive organisational behaviors? a conceptual study of servant leadership, psychological capital, and intention to quit relationship - Brohi, Noor Ahmed; Jantan, Amer Hamzah; Sobia, Zeeshan; Aktar, Muhammad Saood; Pathan, Tayyaba Gul (Research Publishing Academy, 2018)
This study examined the impact of servant leadership, an employee and community focused leadership style on followers’ attitude and behaviour. Specifically, in this paper, we examine how servant leadership and psychological capital may enlighten our understanding of psychological mechanisms that affect follower behaviours. Servant leadership style as penned by Robert Greenleaf that servant leaders guide followers to adopt the behaviour of their leaders by putting others needs above their own. Psychological Capital, a form of positive organisational behaviour, gained much importance in recent years because of its usefulness in producing beneficial results for employees and the whole organisation. From emerging research on servant leadership and based on social exchange theory (SET), we proposed a model contending that servant leaders increase employees’ PsyCap which directly influences Employees’ intention to quit. As proposed, servant leadership will be negatively related to employees’ intention to quit and positively related to PsyCap. PsyCap will mediate the relationship between servant leadership and intention to quit.